El juego cooperativo para desarrollar habilidades sociales en los niños del subnivel inicial 2 de la escuela de educación básica particular Vicente Agustín Aguirre Ruiz, de la ciudad de Loja, periodo académico 2018-2019 - Mena Medina, Daniela Inés (2020)
The present research entitled: THE COOPERATIVE GAME TO DEVELOP SOCIAL SKILLS IN THE CHILDREN OF THE INITIAL SUBNIVEL 2 OF THE VICENTE AGUSIN AGUIRRE RUIZ BASIC EDUCATION SCHOOL, OF THE CITY OF LOJA, ACADEMIC PERIOD 2018-2019, as a general objective was set: the cooperative games that allow to improve the development of social skills of the children of the initial sub-level 2. The methods used were: scientific, inductive-deductive, analytical-synthetic, and descriptive statistics, present in all the research. In order to obtain information on the variables, techniques and instruments were used, such as the survey aimed at teachers of initial sub-level 2, and an assessment scale of Ana Betina Lacunza's social skills, which was applied to children aged 4 to 5 years. , evidencing that 25% have acquired social skills; and most with 75% have not developed their social skills; After applying the workshop of cooperative games "one for all and all for one" there is a 76% increase in the development of social skills. The effectiveness of cooperative games to develop social skills in children of the initial sub-level 2 is concluded, so it is necessary to implement games workshops for educational purposes to improve the development of social skills.